The Influence of Celebrity Effect, Perceived Usefulness, Trust on Attitude Toward Influencers and Its Implications on Impulse Buying - Qastholany, Haniyah; Alfanur, Farah (Economics and Business Journal (ECBIS), 2024)
In the growing world of e-commerce, product promotion and marketing via digital platforms is becoming increasingly important. One strategy that has become a trend in an effort to increase product sales is collaborating with influencers in live sessions on the Shopee platform. This research focuses on analyzing consumer decision strategies to make impulse purchases of products in collaboration with influencers on Shopee Live. SEM-PLS method is used to identify and understand the factors that influence consumer impulse purchasing decisions in the context of products collaborating with influencers. By collecting data through questionnaires from 100 active respondents on the Shopee Live Indonesia platform, this research aims to provide in-depth insight into how influencers influence impulse buying decisions and how live streaming interactions can influence consumer behavior. The findings from this research are expected to provide guidance for e-commerce and marketing industry players to improve promotional strategies and maximize sales potential through live-streaming platforms.